Deficiency of GDP-L-galactose phosphorylase, an enzyme required for ascorbic acid synthesis, reduces tomato fruit yield - Alegre, Matías Leonel (2020)
Reduced GDP-l-galactose phosphorylase expression and deficiency of ascorbic acid content lead to decreased fruit set and yield in tomato plants. Reduced GDP-l-galactose phosphorylase expression and deficiency of ascorbic acid content lead to decreased fruit set and yield in tomato plants. GDP-l-galactose phosphorylase (GGP) catalyzes the first step committed to ascorbic acid synthesis. The participation of GDP-l-galactose phosphorylase and ascorbate in tomato fruit production and quality was studied in this work using two SlGGP1 deficient EMS Micro-Tom mutants. The SlGGP1 mutants display decreased concentrations of ascorbate in roots, leaves, flowers, and fruit. The initiation of anthesis is delayed in ggp1 plants but the number of flowers is similar to wild type. The number of fruits is reduced in ggp1 mutants with an increased individual weight. However, the whole fruit biomass accumulation is reduced in both mutant lines. Fruits of the ggp1 plants produce more ethylene and show higher firmness and soluble solids content than the wild type after the breaker stage. Leaf CO2 uptake decreases about 50% in both ggp1 mutants at saturating light conditions; however, O2 production in an enriched CO2 atmosphere is only 19% higher in wild type leaves. Leaf conductance that is largely reduced in both mutants may be the main limitation for photosynthesis. Sink-source assays and hormone concentration were measured to determine restrictions to fruit yield. Manipulation of leaf area/fruit number relationship demonstrates that the number of fruits and not the provision of photoassimilates from the source restricts biomass accumulation in the ggp1 lines. The lower gibberellins concentration measured in the flowers would contribute to the lower fruit set, thus impacting in tomato yield. Taken as a whole these results demonstrate that ascorbate biosynthetic pathway critically participates in tomato development and fruit production.